PERSEPSI SISWA TERHADAP METODE SIMULASI DAN DISIPLIN SISWA DENGAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Khasanah Khasanah; Alva Alva (Akademika, 2023)
This study aims to determine the relationship between the Simulation Method and Student Internship Learning Outcomes at Setu Bekasi High School. To determine the relationship between the Disciplinary Behavior Method and Student Internship Learning Outcomes at Setu Bekasi High School. To determine the relationship between the Simulation Method and Disciplinary Behavior on Student Internship Learning Outcomes at Setu Bekasi High School. The type of research in this thesis is in the form of quantitative descriptive analysis. The population in this study was 603 students of SMAN Setu, taking random samples so that the sample studied was 85 student respondents. The results show that 1) the correlation coefficient (rxy) = 0.634 indicates that the relationship between X1 and Y has a strong level of relationship. The relationship between 63.4% of the PKN learning outcomes of students at SMA Setu Bekasi can be influenced by the Simulation Method variable 36.6% from external factors. 2) the correlation coefficient (rxy) = 0.510 indicates that the relationship between X2 and Y has a strong level of relationship. 3) The simulation method positively affects students' Internship learning outcomes at SMA Setu Bekasi; the correlation coefficient (rxy) = 0.800 indicates that the relationship between X1, X2, and Y has an extreme level of relationship. Meanwhile, the coefficient of determination from the table above shows the value of R square = 0.641; the correlation value implies that 80% of the student learning outcomes of PKN at Setu Bekasi High School (Y) can be explained by the Simulation Method (X1) and Discipline Behavior (X2) so that it can be said that the relationship between the Simulation Method and Disciplinary Behavior together with the PKN learning outcomes of students at SMA Setu Bekasi is 20%.